Absolute asymptotic stability of solutions of linear parabolic differential equations with delay - Kushnir, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish necessary and sufficient conditions for the absolute asymptotic stability of solutions of linear parabolic differential equations with delay.